THE UNFINISHED EXTRADITION TREATY BETWEEN INDONESIA AND SINGAPORE (2007-2012) - Arselma Trus'tee Audrey (HI 16 UMY 002, 2016)
This article aims to analyze the reason behind the unfinished extradition treaty between Indonesia and Singapore. The author argues that the extradition treaty is not finished yet as the Legislative of Republic Indonesia cannot agree on the Defence Cooperation Agreement (DCA) which is included in the Extradition Treaty. This research has shown that the reason behind the Legislative’s disagreement is the contents in the DCA, which is according to the Legislative, potentially violating the sovereignty of Indonesia. The author use the Graham Allison’s Bureaucratic Politics model to identify how the Legislative disagreement can cause the unfinished Extradition Treaty. This research has applied such approach to analyze the problem in the process of the Extradition Treaty between Indonesia and Singapore. Keywords: Extradition Treaty, Indonesia, Singapore, DCA